First lady of letters : Judith Sargent Murray and the struggle for female independence - Skemp, Sheila L. (Early American studies., 2009)
Thanks to the recent discovery of Judith Sargent Murray's papers--including some 2,500 personal letters--Sheila L. Skemp has documented the compelling story of a talented and most unusual eighteenth-century woman.